The Veil Practice of Ustazah Dayah Jeumala Amal in Terms of the Theory of Social and Legal Change - Muhammad Haikal; Saiful Bahri; Muntazir Fahri (Budapest International Research and Critics University, 2021)
The COVID-19 pandemic has made big changes in the world including Indonesia, Dayah Jeumala Amal which is in Indonesia also has an influence, one of which is the behavior of using the veil of her ustazah. This research is descriptive analytic with mixed types whose sources are obtained from the field and literature. There are two scientific questions, the first is the cause of the use of the veil and the second is the relationship between the use of the veil and changes in the law. The results of the study show that the use of the veil is based on religion and a change in law is the right time to use it.